Learning outcomes and their integration into the Slovenian higher education area - Klara Skubic Ermenc; Borut Mikulec (University of Maribor Press, 2020)
The authors discuss the concept of learning outcome and critically evaluate its definition, translation into the Slovenian language and its implications for curriculum planning in (higher) education. Methodologically, the article is the impact analysis of the process of Europeanisation on the conceptualisation of learning outcomes in European (higher) education. More precisely, it evaluates the impact of the European Qualifications Framework and A Framework for Qualifications of the European Higher Education Area on the contemporary understanding of learning outcomes.